Application of Scanning Magnetic Resonance Imaging in the Diagnosis of Prenatal Placental Implantation and Related Care. (1st June 2022) - Lin, Qiuping; Li, Bizhu; Chen, Shuyun; Lin, Cairu; Lin, Zhixia; Zhang, Fengjiao; Luo, Xiaojiao; Chen, Yulin; Wu, Biyu
Abstract : In order to solve the problem of scanning magnetic resonance imaging in prenatal diagnosis, the application and research of placental implantation have been proposed. Placental implantation is a serious obstetric emergency, which refers to the abnormal attachment of placental villi caused by the dysplasia of decidual basal layer. A study from the United States showed that the incidence of placental implantation in pregnant women during delivery increased from 9.9/30000 to 11.6/20000 from 2006 to 2019, which increased the risk of prenatal or postpartum hemorrhage, hysterectomy, stillbirth, abdominal organ injury, and so on. Clinically, patients can show severe prenatal or postpartum hemorrhage, postpartum placental retention, uterine perforation, and secondary infection, which may seriously endanger the lives of pregnant mothers and fetuses. Placental implantation can also have no obvious symptoms before delivery, which leads to insufficient prenatal diagnosis. Gielchinsky retrospectively studied 410 patients with placental implantation and found that only 9 patients were detected by prenatal ultrasound or magnetic resonance imaging (MRI), and the detection rate was only 6.6%. It can be seen that if the accurate diagnosis of placental implantation can be made before prenatal or symptoms appear, clinical intervention treatment can be carried out in time to reduce the probability of hysterectomy and improve the examination means of patients' prerecovery. At present, studies at home and abroad suggest that it has good clinical application value and research prospect in the clinical diagnosis of placental implantation.